I spy fun house : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Scholastic, 1993)
Rhyming verses ask readers to find hidden objects in the photographs.
"Cartwheel books.".
Publisher's Weekly.
School Library Journal.
Wilson's Children.
2.5
K-3
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles; Picture puzzles